Antimicrobial activity of Acalypha siamensis Oliv. ex Gage - Wiart, C.; Hannah, A.; Yassim, M.; Hamimah, H.; Sulaiman, M. (2004)
The hexane, dichloromethane, ethyl acetate and methanol fractions of leaves of Acalypha siamensis Oliv. ex Gage were evaluated for antibacterial and antifungal activity. The antibacterial activity was more pronounced in the ethyl acetate and methanol extracts. No activity was shown against tested moulds